A phase Ib multiple ascending dose study of the safety, tolerability, and central nervous system availability of AZD0530 (saracatinib) in Alzheimer’s disease - Nygaard, Haakon B; Wagner, Allison F; Bowen, Garrett S; Good, Susan P; MacAvoy, Martha G; Strittmatter, Kurt A; Kaufman, Adam C; Rosenberg, Brian J; Sekine-Konno, Tomoko; Varma, Pradeep; Chen, Kewei; Koleske, Anthony J; et al. (Alzheimer's research & therapy, 2015)
Introduction Despite significant progress, a disease-modifying therapy for Alzheimer’s disease (AD) has not yet been developed. Recent findings implicate soluble oligomeric amyloid beta as the most relevant protein conformation in AD pathogenesis. We recently described a signaling cascade whereby oligomeric amyloid beta binds to cellular prion protein on the neuronal cell surface, activating intracellular Fyn kinase to mediate synaptotoxicity. Fyn kinase has been implicated in AD pathophysiology both in in vitro models and in human subjects, and is a promising new therapeutic target for AD. Herein, we present a Phase Ib trial of the repurposed investigational drug AZD0530, a Src family kinase inhibitor specific for Fyn and Src kinase, for the treatment of patients with mild-to-moderate AD. Methods The study was a 4-week Phase Ib multiple ascending dose, randomized, double-blind, placebo-controlled trial of AZD0530 in AD patients with Mini-Mental State Examination (MMSE) scores ranging from 16 to 26. A total of 24 subjects were recruited in three sequential groups, with each randomized to receive oral AZD0530 at doses of 50 mg, 100 mg, 125 mg, or placebo daily for 4 weeks. The drug:placebo ratio was 3:1. Primary endpoints were safety, tolerability, and cerebrospinal fluid (CSF) penetration of AZD0530. Secondary endpoints included changes in clinical efficacy measures (Alzheimer’s Disease Assessment Scale – cognitive subscale, MMSE, Alzheimer’s Disease Cooperative Study – Activities of Daily Living Inventory, Neuropsychiatric Inventory, and Clinical Dementia Rating Scale – Sum of Boxes) and regional cerebral glucose metabolism measured by fluorodeoxyglucose positron emission tomography. Results AZD0530 was generally safe and well tolerated across doses. One subject receiving 125 mg of AZD0530 was discontinued from the study due to the development of congestive heart failure and atypical pneumonia, which were considered possibly related to the study drug. Plasma/CSF ratio of AZD0530 was 0.4. The 100 mg and 125 mg doses achieved CSF drug levels corresponding to brain levels that rescued memory deficits in transgenic mouse models. One-month treatment with AZD0530 had no significant effect on clinical efficacy measures or regional cerebral glucose metabolism. Conclusions AZD0530 is reasonably safe and well tolerated in patients with mild-to-moderate AD, achieving substantial central nervous system penetration with oral dosing at 100–125 mg. Targeting Fyn kinase may be a promising therapeutic approach in AD, and a larger Phase IIa clinical trial of AZD0530 for the treatment of patients with AD has recently launched. Trial registration ClinicalTrials.gov: NCT01864655 . Registered 12 June 2014.